Overview of The Head CT-Scan in Stroke Patients who was Treated at Muhammadiyah Hospital Palembang - Yusastra, Pratrisna; Indriyani, Indriyani; Utama, Budi (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: Stroke is a collection of symptoms of neurological deficits due to sudden acute disturbance of brain function, both focal and global, caused by blockage or rupture of arteries and veins and proven by imaging and/or reflex pathology. Using CT-Scan, the description of acute phase stroke can be easier and can determine the appropriate treatment criteria for stroke. Purposes: To determine characteristic Head CT-Scan image of stroke patients hospitalized in Muhammadiyah Palembang Hospital. Methods: This study was conducted in a retrospective descriptive manner and obtained a sample of 41 stroke patients according to the inclusion and exclusion criteria using total sampling. Result: In this study, there were 28 patients (68.2%) with ischemic stroke and 13 patients (31.7%) with hemorrhagic stroke. Head CT-Scan image of ischemic stroke shows basal ganglia lesion (28.5%) and the right hemisphere lesions (57.1%) as the most predominant area. Head CT-Scan image of hemorrhagic stroke (58.3%) had intracerebral hemorrhage with the dominant thalamic lesion area (66.6%) and the right hemisphere (58.3%) had the most lesions with 8 patients (66, 6%) had a midline shift. Stroke patients were treated as experienced by the elderly (90.2%) and were dominated by the female sex (63.4%) and are dominated by clinical symptoms of hemiparesis (29.2%). Conclusion: Stroke patients at Muhammadiyah Palembang hospital dominated by ischemic stroke and on head CT Scan image predominantly shows lesions on the right cerebral hemisphere.